Creating pathways for collaboration between Argentina and the UK to utilise microbial biofilms in sustainable agriculture - Patricia L. Abdian; Miguel Cámara; Fabricio D. Cassan; Gabriel Castrillo; Marisa Díaz; Gustavo Gonzalez Anta; Claire Hodge; Jo Slater-Jefferies; Cait E. MacPhee; Enzo Moriconi; Paulina D. Rakowska; Rasmita Raval; et al. (CABI Agriculture and Bioscience)
Abstract Microbial biofilms are complex communities of microorganisms that exist in various environments, including natural and human-built systems and have a significant economic impact on a global scale. In addition to their detrimental impacts, biofilms have been extensively studied for their potential benefits. In agriculture, biofilms are considered key organisational structures of microbes, exploited as biofertilisers, biostimulants, and biocontrol agents, with the potential to enhance soil health and plant growth. Despite ongoing research, there are still large knowledge gaps in the understanding of the mechanisms governing interaction between biofilms and plants, and how these can be manipulated to promote sustainable agriculture. The UK’s National Biofilms Innovation Centre [NBIC] and Argentine researchers have established a dialogue aimed at addressing these gaps and improving agricultural productivity through the integration of new technologies that can promote soil health whilst reducing environmental impact. Future research collaborations between the two countries in this area could have significant benefits for global agricultural innovation and the development of sustainable food systems. This publication takes on a ‘white paper’ format, consolidating complex discussions from a workshop between NBIC and Argentine researchers. It offers a comprehensive summary encompassing the insights, perspectives, and outcomes generated during the discussions among the participants, pinpointing three key priority areas for collaborative activities that were identified: (1) Using plant root biofilm composition as a sensor for soil health and to optimise interventions, (2) Biofilms and soil health resilience in a changing environment, (3) Intelligent seeds and innovative / automated large-scale monitoring systems. For the three identified priority areas, the early engagement of end-users [farmers] will be paramount to maximise technology adoption. Commitment from the governments and support from funding bodies in both countries will be essential for the establishment of robust research programmes and long-term successful collaborations between researchers, industry and end users. Graphical Abstract